Neurocognitive and Behavioral Outcomes of Chinese Survivors of Childhood Lymphoblastic Leukemia - Peng, Liwen; Yang, Lok Sum; Yam, Perri; Lam, Chun Sing; Chan, Agnes Sui-yin; Li, Chi Kong; Cheung, Yin Ting (Frontiers in Oncology, 2021)
Background: Increasing attention has been dedicated to investigate modifiable risk factors of late effects in survivors of childhood cancer. This study aims to evaluate neurocognitive and behavioral functioning in a relatively young cohort of survivors of childhood acute lymphoblastic leukemia (ALL) in Hong Kong, and to identify clinical and socio-environmental factors associated with these outcomes. Methods: This analysis included 152 survivors of childhood ALL who were ≥5 years post-diagnosis (52% male, mean[SD] age 23.5[7.2] years at evaluation, 17.2[7.6] years post-diagnosis). Survivors completed performance-based neurocognitive tests, and reported their emotional and behavioral symptoms using the Child/Adult Behavior Checklist. Socio-environmental variables (living space, fatigue, physical activity, family functioning, and academic stress) were self-reported using validated questionnaires. Clinical variables and chronic health conditions were extracted from medical charts. Multivariable linear modeling was conducted to test identify factors associated with neurocognitive/ behavioral outcomes, adjusting for current age, sex, age at diagnosis and cranial radiation. An exploratory mediation analysis was performed to examine the mediating effects of risk factors on neurocognitive and behavioral outcomes. Results: As compared to population norms, a minority of survivors developed mild-moderate impairment in motor processing speed (36.2%), memory (9.2%) and attention measures (4.0%-10.5%). Survivors also reported attention problems (12.5%), sluggish cognitive tempo (23.7%) and internalizing (depressive, anxiety and somatic) problems (17.1%). A minority developed mild-moderate treatment-related chronic conditions (n=37, 24.3%). As compared to survivors without chronic conditions, survivors with chronic conditions had more executive dysfunction (B=5.09, standard error [SE]=2.05; P=0.014) and reported more attention problems (B=5.73, SE=1.43; P<0.0001). Fatigue and poor family functioning was associated with multiple behavior domains (all P<0.001). A lower level of physical activity was correlated with more self-reported symptoms of inattention (B= -1.12, SE=0.38, P=0.004) and sluggish cognitive tempo (B=-1.22, SE=0.41, P=0.003). Exploratory analysis showed that chronic health conditions were associated with behavioral measures through fatigue as the mediator. Conclusion: The majority of young Chinese survivors of ALL had normal cognitive and behavioral function. Regular monitoring of behavioral function should be performed on survivors who develop treatment-related chronic conditions. Health behavior and socio-environment factors may be potentially modifiable risk factors associated with health outcomes in survivors.